Modified Bessel–Gaussian Vortex Beam with an Adjustable Broken Opening. Issue 1 (6th December 2021) - Yang, Kaibo; Wu, Zhenkun; Zhang, Yagang; Li, Peng; Wen, Feng; Gu, Yuzong
Abstract: In this study, an open‐ring controllable Bessel vortex beam is theoretically and experimentally constructed with a power‐exponent‐phase vortex. Its distribution in the far field after being blocked with obstacles is subsequently investigated. In the far field, the beam exhibits different degrees of the open‐loop effect following adjustments in the phase term of the power exponent. For an obstructed beam, the direction of the open loop is offset by a certain value, and different open‐loop angles can be achieved for different blocking angles. The developed beam can be used to guide particles and avoid obstacles. Abstract : This study theoretically and experimentally demonstrates that in the far field, the reconstructed beam exhibits different degrees of open‐loop effect when the phase term of the power exponent is adjusted, and when the beam is obstructed, the direction of the open loop is offset by a certain amount, and different open‐loop angles can be achieved for different blocking angles.